Analysis of self confidence levels in roller skating athletes - Suryawati Suryawati; Rizki Burstiando Rizki Burstiando; Wasis Himawanto; Budiman Agung Pratama (Sriwijaya Journal of Sport, 2022)
This study aims to analyze the level of self-confidence of athletes at the FIST roller skating club in Tulungagung, with a sample of 13 athletes. The method used in this research is descriptive quantitative non-experimental. The instrument in this study is a closed questionnaire and the scale used is the Likert scale and obtains data from a questionnaire that has been distributed to the sample. The results showed that the self-confidence level of FIST roller skate athletes in Tulungagung was based on 2 factors that influenced the level of self-confidence, namely, external factors obtained the "high" category as many as 7 athletes (54%) and internal factors obtained the "high" category as many as 8 athletes (62%) with an average of 58%. Based on the results of this study, it can be concluded that the FIST Tulungagung roller skate athletes have a high level of self-confidence. This statement can be interpreted that the Tulungagung FIST roller skate athletes have confidence/confidence and are sporty in practising and competing to achieve achievements.